Reception and monitoring of patients diagnosed with eating disorders: a case study at the Family Health Unity Bandeiras, in Anápolis-GO - Melo , Erick Nunes; Carvalho, Karla Cristina Naves de (Seven Editora, 2023)
Eating disorders are psychosocial problems increasingly present in the current scenario, marked by a progressive advance of globalization, which accompanies a discourse aimed at the standardization of bodies. What is preached is that the physical form determines the image that the subject assumes before society, especially women. As a result, many who do not conform to these pre-established standards end up developing psychological dysfunctions that interfere with the way they see their own bodies. Thus, health professionals assume the responsibility to support women diagnosed with this type of problem from their arrival at health units until referral to specialist professionals. Starting from the analytical descriptive method, the present work seeks to investigate how this monitoring happens through the analysis of a case observed in the Family Health Unit Bandeiras, in Anápolis-GO, starting with a brief description of the unit's functioning and starting for a specific discussion about the case studied and about the importance of adequate professional monitoring. DOI:https://doi.org/10.56238/tfisdwv1-184